Clinical efficacy, safety, and cost of nine Chinese patent medicines combined with ACEI/ARB in the treatment of early diabetic kidney disease: A network meta-analysis - Liu, Jiarong; Zhang, Xuehan; Xu, Gaosi (Frontiers in Pharmacology, 2022)
Objectives: To evaluate and compare the efficacy, safety and cost of nine Chinese patent medicines (CPMs) combined with angiotensin-converting enzyme inhibitor (ACEI) or angiotensin receptor blocker (ARB) in treating early diabetic kidney disease (DKD). Design: Systematic review and network meta-analysis. Data sources: PubMed, Embase, Cochrane Library, Web of Science, clinicaltrials. gov, SinoMed, Chinese Biomedicine, China National Knowledge Infrastructure, WanFang and Chongqing VIP Information databases were comprehensively searched from beginning to February 2022. Review Methods: Randomized controlled trials (RCTs) including Bailing Capsule (BLC); Jinshuibao (JSB); Huangkui Capsule (HKC); Compound Xueshuantong Capsule (CXC); Uremic Clearance Granule (UCG); Shenyan Kangfu Tablet (SYKFT); Tripterygium glycosides (TG); Keluoxin Capsule (KLX) and Shenshuaining Tablet (SSNT) combined with ACEI/ARB for patients with early DKD were reviewed. Data synthesis: Two reviewers independently screened articles, extracted data and assessed the risk of bias. Risk ratios (RRs) and mean difference (MD) were reckoned to assess dichotomous variable quantities and continuous variable quantities, respectively. Using the surface under the cumulative ranking curve (SUCRA), we then ranked each therapeutic regime. Results: Ultimately, 160 RCTs involving 13365 patients and nine CPMs were included. UCG showed significantly higher probabilities on urinary albumin excretion rate (UAER) when compared with ACEI/ARB group, with MD of −47 (95%CI) (−57, −37) and SUCRA 98.0%. The CXC group achieved a remarkable improvement in overall response rate (ORR) compared with ACEI/ARB (RR,1.3, 95%CI (1.2, 1.5)) with SUCRA 91.9%. SSNT could significantly superior than ACEI/ARB group in terms of serum creatinine (Scr) (−19 (−26, −12), SUCRA 99.3%) and adverse effects (AEs) (0.46 (0.17, 1.1), SUCRA 82.9%). BLC showed the greatest effectiveness on 24 hours urinary total protein (24h UTP) (−170 (−260, −83), SUCRA 78.5%) and triglyceride (Trig) (−0.89 (−1.2, −0.53), SUCRA 97.0%). Conclusions: UCG and CXC might be the optimum selection for improving UAER and ORR, and SSNT could significantly superior than ACEI/ARB group in terms of Scr and AEs. BLC shows best curative effect on 24h UTP and Trig. TG shows the highest cost-effective among nine CPMs.